HAZOP analysis and reliability assessment of closed loop solar water heater system for residential application - Abd Wahab, Nurul Husna; Kamarudin, Suryani (National Institute of Occupational Safety and Health (NIOSH), 2019)
Solar thermal system or solar water heater system is one of the applications used to produce hot water in the residential sector. This paper describes HAZOP analysis and reliability assessment to evaluates the potential hazard and system probability for the closed loop solar thermal system applied for the residential area. Hazard identification for the main system components is analyzed while Fault Tree Analysis (FTA), Reliability Block Diagram (RBD) and Weibull distributions performed to determine the reliability for the overall system. The result shows that there are 49 potential hazards for the system with failure probability at 0.23822 and the reliability is 0.9693. Subsequently, this study determined the potential hazards for the system which can be anticipated by the residential consumer for the safety aspect. Furthermore, the evaluated reliability result shows that the application of closed loop type solar water heater system at residential premises is highly recommended due to its long lasting operational condition.